2012
DOI: 10.1021/bm2017756
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Responsive Magnetic Core–Shell Nanoparticles for Nonviral Gene Delivery and Cell Separation

Abstract: IntroductionThere exist two main approaches for the functionalization of nanoparticles (NPs) with polymer chains fixed on the NPs' surface. The "grafting-to" method is performed by utilizing polymers bearing suitable functional end groups (anchor groups), which are able to bind to the surface of the particle. Alternatively, the "grafting-from" approach can be used to obtain core-shell nanoparticles. In this case, the initiating moiety is immobilized on the nanoparticle surface and the polymerization takes plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
107
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 71 publications
10
107
1
Order By: Relevance
“…The molecular weight of degrafted PEG brushes from Fe 3 O 4 @SiO 2 @PEG nanoparticles measured by GPC was 125 400 g mol À1 with a polydispersity index of 1.32. By combining the results from TGA and GPC (described in ESI †), 59,60 the density of the initiator Br on the magnetic nanoparticles is evaluated to be approximately 10.5 initiators per nm 2 and the grafting density of PEG brushes was about 0.79 chains per nm 2 . The successful introduction of functional group (amine, phosphate and titanium ion) was confirmed by z potential measurements (Table S1 †) and X-ray photoelectron spectrometry (XPS) analysis (Table S2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight of degrafted PEG brushes from Fe 3 O 4 @SiO 2 @PEG nanoparticles measured by GPC was 125 400 g mol À1 with a polydispersity index of 1.32. By combining the results from TGA and GPC (described in ESI †), 59,60 the density of the initiator Br on the magnetic nanoparticles is evaluated to be approximately 10.5 initiators per nm 2 and the grafting density of PEG brushes was about 0.79 chains per nm 2 . The successful introduction of functional group (amine, phosphate and titanium ion) was confirmed by z potential measurements (Table S1 †) and X-ray photoelectron spectrometry (XPS) analysis (Table S2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…its monomer can be polymerized in differently controlled manners like atom transfer radical polymerization (ATRP), [7][8][9] and reversible addition-fragmentation chain transfer polymerization. 10,11 However, the transfection efficiency and cytotoxicity of PDMAEMA go hand-in-hand with increasing the molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…Majewski et al 6 have reported the preparation of magnetic-responsive nanoparticles prepared via surface-initiated atom transfer radial polymerization of 2-(N,N-dimethylamino)ethyl methacrylate from Fe 2 O 3 nanoparticles. Dai et al 7 have reported coreshellcorona-type magneticresponsive particles prepared from diblock copolymers composed of poly(acrylic acid) and polystyrene decorated surfaces on iron oxide particles.…”
mentioning
confidence: 99%